Smashing jQuery - Rutter, Jake (Chichester, England : Wiley Publishing, 2011)
"From the world?s most popular resource for web designers and developer?s comes the ultimate guide to jQuery. Begins with an exploration of fundamental jQuery concepts such as Document Object Model (DOM) scripting. Explores writing "Don?t Repeat Yoursefl" (DRY) to gain a comprehensive understanding of these imperative modern techniques and best practices Shows how jQuery enables the user to adhere to these modern best practices with ease The succeeding chapters discuss a specific part of jQuery development such as manipulating the DOM, working with Ajax, and adding slick animation effects through tutorial style learning approach that utilizes working examples to explore the concept The books caps off by discussing popular ways of extending the core jQuery library with pugins and building web interfaces using jQuery UI.-- Provided by publisher
The book caps off by discussing popular ways of extending the core jQuery library with plugins and building web interfaces using jQuery UI"-- Provided by publisher
1. Introducing jQuery -- 2. Getting started with jQuery -- 3. Using selectors, filters, and CSS: jQuery at its core -- 4. Working with events -- 5. Making your site come alive with effects -- 6. Improving navigation: menus, tabs, and accordions -- 7. Creating interactive and exciting tables -- 8. Creating advanced forms with jQuery -- 9. Working with dynamic data and ajax -- 10. Creating and using jQuery plug-Ins -- 11. Developing for the mobile web with jQuery -- 12. Finding jQuery resources
Includes index
Keywords: HTML (Document markup language); JavaScript (Computer program language); Query languages (Computer science); Subroutines (Computer programs)